Invasive lactobacillus infection in pediatric patients in a tertiary center in Taiwan – 16 years’ experience and literature review - Wei-Hung Wu; Chien-Chung Lee; Yi-Ching Chen; Ming-Chou Chiang; Cheng-Hsun Chiu (Pediatrics and Neonatology, 2024)
Background: Lactobacilli are common microorganisms in the human body. Some species were used as probiotics supplement for many purposes such as preventing necrotizing enterocolitis, or improving allergic diseases or diarrhea. Previously, Lactobacillus infection was thought of as contamination due to its low pathogenicity. However, there have been reports of invasive Lactobacillus infection in immunocompromised patients or patients with comorbidities. The purpose of this study was to analyze the clinical characteristics, antibiotic treatment and outcomes of pediatric patients with invasive Lactobacillus infection. Methods: We retrospectively reviewed pediatric patients diagnosed with invasive Lactobacillus infection between 2004 and 2020. Invasive Lactobacillus infection was diagnosed if sterile sites yielded Lactobacillus spp. Clinical manifestations, chronic diseases, potential predisposing factors, medical treatments, antimicrobial susceptibility tests and outcomes were recorded. Results: Fifteen pediatric patients were diagnosed with invasive Lactobacillus infection, accounting for 2.4% of total invasive Lactobacillus infections during the 16-year period. Eleven infections were bacteremia, two were intra-abdominal infections, and two were biliary tract infections. Fever was the most common symptom. Potential predisposing factors were immunocompromised status, central venous device, prolonged antibiotics use and receiving supplemented probiotics for at least one week. All patients survived with favorable outcomes. Most pathogens were identified as Lactobacillus spp, and two were Lactobacillus rhamnosus, which were related to supplemented probiotics. The antimicrobial susceptibility tests showed that Lactobacilli were all sensitive to ampicillin but resistant to glycopeptides. Conclusion: Invasive Lactobacillus infections in pediatric patients were rare. Despite its low pathogenicity, Lactobacillus could cause invasive infection in those immunocompromised patients.